On a System of Dirac Differential Equations with Discontinuity Conditions Inside an Interval - Amirov, R. Kh. (Ukrains’kyi Matematychnyi Zhurnal, 2005)
We study representations of solutions of the Dirac equation, properties of spectral data, and inverse problems for the Dirac operator on a finite interval with discontinuity conditions inside the interval.